Thallium pi-cation complexation by calix[4]tubes: (205)Tl NMR and x-ray evidence. - Matthews, SE; Rees, N; Felix, V; Drew, MG; Beer, P (2003)
Thallium cation complexation by calix[4]tubes has been investigated by a combination of (205)Tl, (1)H NMR and ES MS demonstrating the solution formation of a dithallium complex in which the cations are held in the calix[4]arene cavities. In addition, the structure of the complex has been determined in the solid state revealing the cations to be held exclusively by pi-cation interactions. Furthermore, this crystal structure has been used as the basis for molecular dynamics simulations to confirm that binding of the smaller K(+) cation in the calix[4]tube cryptand like array occurs via the axial route featuring a pi-cation intermediate.